2009
DOI: 10.1080/15575330903001430
|View full text |Cite
|
Sign up to set email alerts
|

Making Healthy Choices to Reduce Childhood Obesity: Community Capitals and Food and Fitness

Abstract: Attention has shifted to environmental causes of health status, particularly obesity, now defined as a worldwide epidemic. Moving from medical and educational models of intervention, this approach focuses on how changes in the social and physical environment enhance families and individuals to make health choices. Using illustrations from current intervention programs, we demonstrate how a community capitals approach can help identify what is in place to enable healthy food and exercise choices, and how those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…:360). Augmenting these findings that report stratified patterns of diet‐related poor health outcomes (e.g., obesity, diabetes, hypertension) is a copious body of health and nutrition research found in scholarly journals (see for example Cummins and Macintyre ; Flora and Gillespie ; Moore and Diez Roux ; Nestle et al. ; Schafft et al.…”
Section: Healthy Food Availability and Poverty In The United Statesmentioning
confidence: 88%
See 1 more Smart Citation
“…:360). Augmenting these findings that report stratified patterns of diet‐related poor health outcomes (e.g., obesity, diabetes, hypertension) is a copious body of health and nutrition research found in scholarly journals (see for example Cummins and Macintyre ; Flora and Gillespie ; Moore and Diez Roux ; Nestle et al. ; Schafft et al.…”
Section: Healthy Food Availability and Poverty In The United Statesmentioning
confidence: 88%
“…Hunger-relief initiatives are widespread and a significant portion of federal and state relief efforts. Furthermore, connections between poor food availability (presence of stores), poor accessibility (ability to get to stores), and poor health have been established by numerous empirical reports (Beaulac, Kristjansson, and Cummins 2009;Cummins and Macintyre 2006;Flora and Gillespie 2009;Moore and Diez Roux 2006;Nestle et al 1998;Pampel, Krueger, and Denney 2010;Schafft, Jensen, and Hinrichs 2009). Most recently, these studies and relief initiatives have turned toward analyses of availability of fresh and nutritious foods and efforts to promote gardening and local food production.…”
Section: Introductionmentioning
confidence: 99%
“…An extension of grower-consumer relationships is illustrated in farmers' market environments, where food growers showcase their produce, seek to educate consumers, or simply engage in conversations that contribute to the critical social interaction aspect that has all but disappeared in the more rigid and impersonal supermarket chain environments. Finally, today's emphasis in many consumer environments concerning the availability of local foods (Ostrom, 2006) or the promotion of healthier eating habits (Flora & Gillespie, 2009) further emphasize the strategic role of farmers' markets in promoting community development in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Walkable scores for selected three east Texas counties: physical activity and policy implications. International Journal of Human Sciences, 12(2), 674-687. doi:10.14687/ijhs.v12i2.3256 678 community issues such as poverty reduction and rural development in dry areas (Flora & Thiboumery, 2005), community resilience (Magis, 2010), sustainable livelihoods and community change (Gutierrez-Montes, Emery & Fernandez-Baca, 2009), childhood obesity (Flora & Gillespie, 2009), community transformation (Emery & Flora, 2006), and measuring success in communities (Jacobs, 2007). These studies resonate with the premise of this study about the walkability in selected east Texas counties.…”
Section: Introductionmentioning
confidence: 99%